2017
DOI: 10.1021/acs.macromol.6b02331
|View full text |Cite
|
Sign up to set email alerts
|

Self-Assembly Kinetics of Amphiphilic Dendritic Copolymers

Abstract: The self-assembly process of amphiphilic dendritic copolymers (ADPs) with a hydrophilic core and hydrophobic shell was investigated via laser light scattering. The self-assembly occurs via a fast step and a slow step with different relaxation times. At the critical micelle concentration (CMC), the fusion of small micelles results in the rapid increase of the micelle size in the fast step. The slow step is associated with equilibrium through the fission and fusion of the micelles. The micelle size increases wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
1

Year Published

2017
2017
2020
2020

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 44 publications
1
8
1
Order By: Relevance
“…S3). The Rh of the micelles increases with the unimer concentration in the solvent mixture of chloroform and methanol as previously reported [22]. However, in the present system, the influence of the unimer concentration on the micelle size is different.…”
Section: The Micellization Kinetics Of the Adpssupporting
confidence: 83%
See 2 more Smart Citations
“…S3). The Rh of the micelles increases with the unimer concentration in the solvent mixture of chloroform and methanol as previously reported [22]. However, in the present system, the influence of the unimer concentration on the micelle size is different.…”
Section: The Micellization Kinetics Of the Adpssupporting
confidence: 83%
“…In this work, in order to track the aggregation processes from unimers to the final equilibrium micelles of the ADPs, after filtration the temperature was controlled to a critical value at which all the ADPs can undergo micellization. Also, in the previous reports [22], the influence of concentration on the relaxation times is contrary to the block copolymers and by 6 analysing the micelle concentration, we found that the increasing relaxation time is caused by the decreasing micelle concentration with increasing unimer concentration.…”
Section: Introductionmentioning
confidence: 39%
See 1 more Smart Citation
“…The dynamics of phase transitions and morphology formation in inhomogeneous polymeric systems is of fundamental as well as great practical interest [1][2][3][4][5][6]. Due to the large length and time scales on which these processes take place, simulation studies usually rely on coarse-grained models.…”
Section: Introductionmentioning
confidence: 99%
“…The DPD method was proven to be an effective mesoscopic simulation tool to study fluid events occurring at millisecond timescales and micrometer length scales via by tracking the motion of coarse-grained particles (composed of a group of atoms or molecules). Many researchers studied the thermodynamic and morphological behavior of polymers using the DPD method, for example, self-assembly of dendritic copolymers [25][26][27], micelle fusion or vesicle formation [28,29], and nanocomposite systems [30][31][32][33].…”
Section: Dpd With the Slip-spring Modelmentioning
confidence: 99%